2018
DOI: 10.1038/s41598-018-30932-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacterial microbiota compositions along the intestinal tract in pigs and their interactions and functions

Abstract: In addition to its value in meat production, the pig is an interesting animal model for human digestive tract studies due to its physiological similarities. The aim of this study was to describe the microbiome composition, distribution and interaction along the Iberian pig intestinal tract and its role in whole-body energy homeostasis. The V3-V4 region of the 16S rRNA gene was amplified and sequenced from the microbiomes of five gut sections (duodenum, jejunum, ileum, and proximal and distal colon) in thirteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
109
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(136 citation statements)
references
References 59 publications
(96 reference statements)
23
109
4
Order By: Relevance
“…Moreover, in the present study we also confirmed that mucosa samples have higher richness than lumen samples regardless of the location in the gut tract (82,85,88). The three most abundant phyla determined in this study: Firmicutes, Bacteroidetes, and Proteobacteria also matched what is always reported for pigs at that age (73,79,82,86,87,89). In terms of behavioral traits, GLN and A groups behaved similarly and were different from NA pigs, while in terms of microbiota composition the two groups were contrasted.…”
Section: Streptococcus D14supporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, in the present study we also confirmed that mucosa samples have higher richness than lumen samples regardless of the location in the gut tract (82,85,88). The three most abundant phyla determined in this study: Firmicutes, Bacteroidetes, and Proteobacteria also matched what is always reported for pigs at that age (73,79,82,86,87,89). In terms of behavioral traits, GLN and A groups behaved similarly and were different from NA pigs, while in terms of microbiota composition the two groups were contrasted.…”
Section: Streptococcus D14supporting
confidence: 89%
“…tract (79)(80)(81)(82)(83)(84)(85). In term of microbial composition, ileum samples were drastically different from caecum and colonic samples which were highly similar (81,83,84,86,87).…”
Section: Streptococcus D14mentioning
confidence: 97%
“…In contrast, the colon is mainly associated with carbohydrate fermentation, and increases the nutrient availability to the host through fermentation of otherwise indigestible polysaccharides, such as dietary fiber (Richards et al, 2005;Quan et al, 2018). The fermentation results in the production of short chain fatty acids (SCFAs) and other metabolites essential for maintaining the gut epithelium (Crespo-Piazuelo et al, 2018). The production of SCFA can be up-or down-regulated by altering the diet, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacillus spp. are Gram-positive facultative anaerobes that create an abundant bacterial group in human and pig microbiota in the distal small intestine and colon [39,40] . A strain-specific beneficial effect of lactobacilli is determined by high variability in composition of cell wall polysaccharides, peptidoglycan, and teichoic acids, membrane lipoproteins and lipoteichoic acids that can differentially induce the host immune response [41].…”
Section: Introductionmentioning
confidence: 99%